Dual-ion gel electrolyte, preparation method thereof and dual-ion battery

By using dual-ion gel electrolytes and potassium-based Prussian blue positive electrode materials in potassium-ion batteries and combining magnesium metal negative electrodes, the shortcomings in potassium-ion batteries in terms of energy density, safety and cycle life are solved, and the improvement of high energy density, safety and rate performance is achieved.

CN119684637APending Publication Date: 2025-03-25中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411780919.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing potassium ion batteries have shortcomings in terms of energy density, cycle life and safety, especially the electrochemical activity and stability of the positive electrode materials need to be improved. The electrolyte is easily decomposed at high temperatures, and the negative electrode materials are prone to volume expansion during charging and discharging.

Method used

A double-ion gel electrolyte is used to prepare gel electrolyte by mixing potassium salt and magnesium salt, and a composite positive electrode material is prepared by mixing potassium Prussian blue with conductive substances, and magnesium metal is used as the negative electrode material.

Benefits of technology

It achieves high energy density and improves the safety and rate performance of the battery. The deposition of magnesium solves the safety problems of metal dendrites, shortens the ion transfer path, and improves the cycling stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684637A_ABST
    Figure CN119684637A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a dual-ion gel electrolyte, a preparation method thereof and a dual-ion battery. The preparation method comprises the following steps: 1) adding potassium salt and magnesium salt into poly (sodium p-styrenesulfonate) (PSS) to form a mixed solution; (2) adding poly (diallyldimethylammonium chloride) PDADMAC into the mixed solution to form a swelling aggregate; and 3) stirring the swelled aggregate at a high temperature to redissolve the prepared aggregate, and dialyzing after dissolution to obtain the double-ion-containing PSS / PDADMAC hydrogel. The gel electrolyte is prepared by mixing the potassium salt and the magnesium salt, compared with a single ion, the energy density can be improved, the safety problem of metal dendritic crystals is solved through deposition of magnesium, and the hybrid metal ion battery (HMIB) can shorten the ion transfer path and improve the rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a dual-ion gel electrolyte and a preparation method thereof, and a dual-ion battery. Background Art

[0002] With the gradual upgrading of social energy structure and the rapid development of renewable energy generation and smart grid, the requirements for high safety, high energy density, high power density and low cost of battery energy storage systems are constantly increasing. Due to the high cost and limited reserves of lithium (the relative abundance in the earth's crust is only 200ppm) and its safety issues, it is still challenging for lithium-ion batteries to be used sustainably in future products. LIBs (lithium-ion batteries) have serious safety hazards, and because Li metal cannot be used directly as an anode, their energy density is also limited. In addition, the shortage of lithium resources and the imbalance of global distribution have severely restricted the long-term development of lithium-ion energy storage devices. Therefore, finding a suitable lithium substitute has become an important topic in the field of electrochemical energy storage.

[0003] Monovalent Na, K and other multivalent metal elements, such as Mg, Zn, Ca and Al, have attracted great attention. Among them, potassium ion batteries are regarded as a promising type of battery due to their advantages such as abundant raw materials, long cycle life and low cost.

[0004] Potassium-ion batteries are batteries that use potassium ions as charge carriers and achieve charging and discharging through the movement of potassium ions between the positive and negative electrodes. Compared with traditional lithium-ion batteries, potassium-ion batteries have higher operating voltages and greater energy density, so they have broad applications in electric vehicles, energy storage systems and other fields.

[0005] Existing potassium ion batteries mainly use layered oxides as positive electrode materials, such as KCoO 2 , KFeO2, etc. These materials have high electrochemical activity and stability. At the same time, carbon materials such as graphite are also widely used in the negative electrode of potassium ion batteries because they have good electronic conductivity and large interlayer spacing, which can effectively embed and extract potassium ions. In addition, the electrolyte is an important component of potassium ion batteries, which directly affects the electrochemical performance and safety of the battery. At present, the commonly used potassium ion battery electrolyte is mainly composed of potassium salts (such as KP F6 , KC l O 4 A mixed solution consisting of organic solvents (such as EC, DEC, etc.) and organic solvents (such as EC, DEC, etc.).

[0006] However, there are many problems with the above schemes: First, the electrochemical activity and stability of existing potassium ion battery cathode materials need to be improved, which limits the energy density and cycle life of the battery. Secondly, the electrolyte of potassium ion batteries is easy to decompose at high temperatures, resulting in a decrease in the safety performance of the battery. In addition, the negative electrode material of potassium ion batteries is prone to volume expansion during the charging and discharging process, which also affects the cycle stability of the battery. Therefore, how to design and develop high-performance, safe and stable potassium ion batteries is still an important issue in the current battery field. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a dual-ion gel electrolyte and a preparation method thereof and a dual-ion battery.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a dual-ion gel electrolyte comprises the following steps: 1) adding potassium salt and magnesium salt into poly (sodium p-styrene sulfonate) (PSS) to form a mixed solution; 2) adding poly (dimethyldiallyl ammonium chloride) (PDADMAC) into the mixed solution to form a swollen aggregate; 3) stirring the swollen aggregate at high temperature to dissolve the prepared aggregate, and performing dialysis after dissolution to obtain a PSS / PDADMAC hydrogel containing dual ions.

[0010] The molar ratio of the potassium salt and the magnesium salt in step 1) is (1-3):(3-5); preferably 3:5.

[0011] The potassium salt is one of potassium hexafluorophosphate, potassium chloride, potassium fluoride, potassium sulfate, potassium carbonate, potassium phosphate, potassium nitrate, potassium difluorooxalatoborate, potassium pyrophosphate, potassium dodecylbenzenesulfonate, and potassium dodecyl sulfate, or a mixture thereof; the magnesium salt is one of lithium hexafluoromagnesiumate, magnesium bistrifluoromethanesulfonyl imide, and magnesium perchlorate, or a mixture thereof.

[0012] In step 2), the molar ratio of PDADMAC to PSS is (1-4): (6-8); preferably 3:7; preferably, the molecular weight of PDADMAC is Mw 200,000 g / mol xx, and the molecular weight of PSS is Mw 70,000 g / mol;.

[0013] In step 3), the high temperature is 30-80° C., preferably 70° C., and the stirring time is 1-3 h, preferably 2 h.

[0014] The present invention also includes a dual ion gel electrolyte obtained by the preparation method.

[0015] The present invention also includes a metal ion battery, comprising a positive electrode, a negative electrode and the double ion gel electrolyte.

[0016] The positive electrode comprises a positive electrode active material, a conductive agent and a binder; preferably, the conductive agent is CNT; preferably, the binder is PVDF.

[0017] The positive electrode active material is prepared by mixing a conductive material with a potassium Prussian blue material, performing a hydrothermal reaction, ion separation and precipitation, and calcining to obtain the positive electrode active material;

[0018] Preferably, the conductive material is one of graphene oxide, KPA100 or acetylene black;

[0019] The ratio of the conductive material to the potassium Prussian blue material is 1:9; the temperature of the hydrothermal reaction is 100-180°C, and the time is 6-24h; preferably 120°C and 12h; the temperature of the calcination is 600-1000°C, and the time (range is 6-24h; preferably 800°C and 12h.

[0020] The potassium-based Prussian blue material is KxM[Fe(CN) 6 ]1-y·□·zH 2 O, where □ is a vacancy, M is one or more of Mn, Fe, Co, Ni, Cu, and Zn, 0<x≤2, 0≤y<1, 0≤z≤5;

[0021] Preferably, the potassium Prussian blue material is K 1.9 Mn 0.8 Fe 0.2 [Fe(CN) 6 ] 0.96 0.8H 2 O,.

[0022] Preferably, the potassium Prussian blue material is prepared in the following manner: 4 Fe(CN) 6 ·3H 2 O solution was added with MnSO 4 The solution is mixed, the resulting solution is washed with water and ethanol, and dried to obtain a potassium Prussian blue material.

[0023] The negative electrode is magnesium metal. Compared with the prior art, the beneficial effects of the present invention are:

[0024] The present invention provides a magnesium-potassium mixed metal ion battery with high energy density, high safety and high rate. By mixing potassium salt and magnesium salt to prepare gel electrolyte, the energy density can be improved compared with single ion, and the deposition of magnesium solves the safety problem of metal dendrites. In addition, the mixed metal ion battery (HMI B) can shorten the ion transfer path and improve the rate performance. During charging, K +Ions are extracted from the cathode and diffuse into the electrolyte, shortening the transfer path. At the same time, multivalent ions Mg 2+ Deposited on the metal anode, due to its redox potential higher than K + The redox potential of ions is high, and multivalent ions are preferentially deposited on the anode, alleviating the Mg 2+ The problem of slow diffusion kinetics of ions in solid phase.

[0025] The positive electrode active material is prepared by mixing potassium-based Prussian blue with a conductive substance to obtain a composite positive electrode material. The selected conductive substance has an ultra-large specific surface area, a porous structure and good conductivity, which can make up for the structural defects of the positive electrode during the charging and discharging process and store as many potassium ions as possible. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a gel state diagram of Example 1-3;

[0027] Figure 2 It is a circular side view of the embodiment and the comparative example. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0029] Embodiment 1:

[0030] Preparation of positive electrode: 4 Fe(CN) 6 ·3H 2 5M MnSO was added dropwise to a 1 mol / L aqueous solution. 4 The solution was mixed and stirred for 10 hours, the obtained solution was centrifuged 3 times with water and ethanol respectively, and placed in a vacuum drying oven at 100°C and heated for 12 hours to obtain potassium Prussian blue material K 1.9 Mn 0.8 Fe 0.2 [Fe(CN) 6 ] 0.96 0.8H 2 O.

[0031] Graphene oxide was added to ethanol solvent and ultrasonicated for 30 minutes to prepare a 2 mg / ml suspension, and 2 mmol potassium Prussian blue material was added. The hydrothermal synthesis method was 120°C for 12 hours, and then centrifuged and placed in a tubular furnace for high-temperature calcination at 800°C. After 12 hours, the temperature was naturally cooled to 25°C and placed in a freeze dryer to obtain the positive electrode active material.

[0032] The positive electrode active material: CNT: PVDF are mixed in the ratio of 8:1:1, coated on the current collector, dried and rolled to obtain the positive electrode.

[0033] The negative electrode is magnesium metal.

[0034] Preparation of electrolyte: 50 mL of 0.3 mol PSS (sodium poly(p-styrene sulfonate), Mw 70,000 g / mol) containing a mixed solution of 3 M KOTF and 5 M MgCl was prepared in a beaker, and then 0.7 mol 20 wt% PDADMAC (poly(dimethyldiallylammonium chloride), Mw 200,000 g / mol) solution was slowly added to form a swollen aggregate 1. Then, the swollen aggregate 1 was dissolved by stirring at 70°C for 2 h, and then dialyzed in a deionized water bath for 24 h using a dialysis membrane tube to obtain a PSS / PDADMAC hydrogel electrolyte 1. The gel state is shown in FIG. Figure 1 .

[0035] The molar ratio of KOTF to MgCl can be 1:3, 1:5, 1:1, or 3:5, and 3:5 is used as a preferred example in the present application.

[0036] Battery preparation: Assemble button cells in a glove box, assemble the positive electrode, negative electrode, and electrolyte 1 into a battery, and the battery number is 1. Battery 1 is tested for charge and discharge cycles at 25°C, current of 0.5C, and voltage of 2.5-4.7V. The test data is shown in Figure 2 .

[0037] Example 2

[0038] The difference between Example 2 and Example 1 is that the preparation of the electrolyte is different, and the molar ratio of PSS to PDADMAC in the electrolyte is different. Specifically, the following steps are adopted:

[0039] Preparation of electrolyte: 50 mL of 0.2 mol PSS (sodium poly(p-styrene sulfonate)) containing a mixed solution of 3 M KOTF and 5 M MgCL was prepared in a beaker, and then 0.8 mol 20 wt% PDADMAC (poly(dimethyldiallyl ammonium chloride)) solution was slowly added to form swollen aggregate 2. Then, swollen aggregate 2 was dissolved by stirring at 70 °C for 2 h, and then dialyzed in a deionized water bath for 24 h using a dialysis membrane tube to obtain PSS / PDADMAC hydrogel electrolyte 2. The gel state is shown in FIG. Figure 1 .

[0040] Example 3

[0041] The difference between Example 2 and Example 1 is that the preparation of the electrolyte is different, and the molar ratio of PSS to PDADMAC in the electrolyte is different. Specifically, the following steps are adopted:

[0042] Preparation of electrolyte: 50 mL of 0.4 mol PSS (sodium poly(p-styrene sulfonate)) containing a mixed solution of 3 M KOTF and 5 M MgCL was prepared in a beaker, and then 0.6 mol 20 wt% PDADMAC (poly(dimethyldiallyl ammonium chloride)) solution was slowly added to form swollen aggregate 3. Then, the swollen aggregate 3 was dissolved by stirring at 70°C for 2 h, and then dialyzed in a deionized water bath for 24 h using a dialysis membrane tube to obtain PSS / PDADMAC hydrogel electrolyte 3. The gel state is shown in FIG. Figure 1 .

[0043] Figure 1 The gel state obtained in Examples 1-3 is shown. It can be seen from the figure that the electrolyte in bottle No. 2 (PSS:PDADMAC molar ratio is 3:7) is in a gel state, and there is no liquid in the bottle; therefore, the gel electrolyte prepared in Example 1 is selected for the following experiment.

[0044] Example 4

[0045] The difference between Example 4 and Example 1 is that the preparation method of the positive electrode active material is different, and specifically the following steps are adopted:

[0046] Preparation of positive electrode: 4 Fe(CN) 6 ·3H 2 5M MnSO4 solution was added dropwise to a 1 mol / L aqueous solution, and the mixture was stirred for 10 h. The resulting solution was centrifuged 3 times with water and ethanol respectively, and heated in a vacuum drying oven at 100°C for 12 h to obtain potassium Prussian blue material K 1.9 Mn 0.8 Fe 0.2 [Fe(CN) 6 ] 0.96 0.8H 2 O. KPA100 was added to an ethanol solvent and ultrasonicated for 30 minutes to prepare a 2 mg / ml suspension, and 2 mmol of potassium Prussian blue material was added. The hydrothermal synthesis method was 120°C for 12 hours, and then centrifuged and placed in a tube furnace for high-temperature calcination at 800°C. After 12 hours, the temperature was naturally cooled to 25°C and placed in a freeze dryer to obtain the composite positive electrode material 2. Positive electrode material 2: CNT: PVDF were mixed in a ratio of 8:1:1, coated on the current collector, dried, and rolled to obtain the positive electrode sheet 2.

[0047] Example 5

[0048] The difference between Example 5 and Example 1 is that the preparation method of the positive electrode active material is different, and specifically the following steps are adopted:

[0049] Preparation of positive electrode: 4 Fe(CN)6 ·3H 2 5M MnSO was added dropwise to a 1 mol / L aqueous solution. 4 The solution was mixed and stirred for 10 hours, the obtained solution was centrifuged 3 times with water and ethanol respectively, and placed in a vacuum drying oven at 100°C and heated for 12 hours to obtain potassium Prussian blue material K 1.9 Mn 0.8 Fe 0.2 [Fe(CN) 6 ] 0.96 0.8H 2 O. Add acetylene black to ethanol solvent and ultrasonicate for 30 minutes to prepare a 2mg / ml suspension, add 2mmol potassium Prussian blue material, hydrothermally synthesize at 120℃ for 12h, centrifuge, put in a tube furnace for high-temperature calcination at 800℃, cool naturally to 25℃ after 12h, and put in a freeze dryer to obtain composite positive electrode material 3. Positive electrode material 3: CNT: PVDF are mixed in a ratio of 8:1:1, coated on the current collector, dried, and rolled to obtain positive electrode sheet 3.

[0050] Comparative Example 1

[0051] The difference between Example 1 and Example 4 is that the positive electrode active material is a common potassium Prussian blue material K prepared without adding a conductive agent. 1.9 Mn 0.8 Fe 0.2 [Fe(CN) 6 ] 0.96 0.8H 2 O.

[0052] Comparative Example 2

[0053] The difference between Comparative Example 2 and Example 1 is that only potassium salt KOTF exists in the electrolyte, and only single potassium ions are embedded and extracted.

[0054] Preparation of electrolyte: 50 mL of 0.3 mol PSS (sodium poly(p-styrene sulfonate), Mw 70,000 g / mol) containing 3 M KOTF was prepared in a beaker, and then 0.7 mol of 20 wt% PDADMAC (poly(dimethyldiallylammonium chloride), Mw 200,000 g / mol) solution was slowly added to form swollen aggregate 1. Then, swollen aggregate 1 was dissolved by stirring at 70° C. for 2 h, and then dialyzed by dialysis in a deionized water bath for 24 h using a dialysis membrane tube to obtain a PSS / PDADMAC hydrogel electrolyte.

[0055] Comparative Example 3

[0056] The difference between Comparative Example 3 and Example 1 is that the potassium-based Prussian blue in the positive electrode is replaced with magnesium-based Prussian blue Mg 4[Fe(CN) 5 ] 3 , only magnesium salt MgCl exists in the electrolyte;

[0057] Preparation of electrolyte: 50 mL of 0.3 mol PSS (sodium poly(p-styrene sulfonate), Mw 70,000 g / mol) containing 5 M MgCL was prepared in a beaker, and then 0.7 mol of 20 wt% PDADMAC (poly(dimethyldiallylammonium chloride), Mw 200,000 g / mol) solution was slowly added to form swollen aggregate 1. Then, swollen aggregate 1 was dissolved by stirring at 70° C. for 2 h, and then dialyzed by dialysis in a deionized water bath for 24 h using a dialysis membrane tube to obtain a PSS / PDADMAC hydrogel electrolyte.

[0058] Table 1 Energy density comparison

[0059] sample Cathode Materials Electrolyte salts Specific energy (Ah / g) Example 1 MnSO4+graphene oxide 3M KOTF and 5M MgCl 185 Example 4 <![CDATA[MnSO 4 +KPA100]]> 3M KOTF and 5M MgCl 173 Example 5 <![CDATA[MnSO 4 +Acetylene Black]]> 3M KOTF and 5M MgCl 160 Comparative Example 1 <![CDATA[MnSO 4 ]]> 3M KOTF and 5M MgCl / Comparative Example 2 <![CDATA[MnSO 4 +Graphene Oxide]]> 3M KOTF 150 Comparative Example 3 <![CDATA[Mg 4 [Fe(CN) 5 ] 3 ]]> 5M MgCl 140

[0060] Table 1 shows the energy density comparison of the embodiment and the comparative example. It can be seen from Table 1 that due to the large specific capacity and large specific surface area of ​​graphene, ions can be better embedded and de-embedded, resulting in a large specific energy in Example 1, and it can also make up for the defects of the structure of the positive electrode active material itself. In summary, the present invention provides a high energy density, high safety, and high rate magnesium-potassium mixed metal ion battery. By mixing potassium salt and magnesium salt to prepare a gel electrolyte, the energy density can be improved compared to a single ion, and the deposition of magnesium solves the safety problem of metal dendrites, and the mixed metal ion battery (HMI B) can shorten the ion transfer path and improve the rate performance. During charging, K + Ions are extracted from the cathode and diffuse into the electrolyte, shortening the transfer path. At the same time, multivalent ions Mg 2+ Deposited on the metal anode, due to its redox potential higher than K + The redox potential of ions is high, and multivalent ions are preferentially deposited on the anode, alleviating the Mg 2+ The problem of slow diffusion kinetics of ions in solid phase.

[0061] The positive electrode active material is prepared by mixing potassium-based Prussian blue with a conductive substance to obtain a composite positive electrode material. The selected conductive substance has an ultra-large specific surface area, a porous structure and good conductivity, which can make up for the structural defects of the positive electrode during the charging and discharging process and store as many potassium ions as possible.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a dual-ion gel electrolyte, characterized in that: The method comprises the following steps: 1) adding potassium salt and magnesium salt into poly (sodium p-styrene sulfonate) PSS to form a mixed solution; 2) adding poly (dimethyldiallyl ammonium chloride) PDADMAC into the mixed solution to form a swollen aggregate; 3) stirring the swollen aggregate at high temperature to dissolve the prepared aggregate, and performing dialysis after dissolution to obtain a PSS / PDADMAC hydrogel containing dual ions.

2. The method for preparing a dual ion gel electrolyte according to claim 1, characterized in that: The molar ratio of the potassium salt and the magnesium salt in step 1) is (1-3):(3-5); preferably 3:

5.

3. The method for preparing a dual ion gel electrolyte according to claim 1, characterized in that: The potassium salt is one of potassium hexafluorophosphate, potassium chloride, potassium fluoride, potassium sulfate, potassium carbonate, potassium phosphate, potassium nitrate, potassium difluorooxalatoborate, potassium pyrophosphate, potassium dodecylbenzenesulfonate, and potassium dodecyl sulfate, or a mixture thereof; the magnesium salt is one of lithium hexafluoromagnesiumate, magnesium bistrifluoromethanesulfonyl imide, and magnesium perchlorate, or a mixture thereof.

4. The method for preparing a dual ion gel electrolyte according to claim 1, characterized in that: In step 2), the molar ratio of PDADMAC to PSS is (1-4): (6-8); preferably 3:7; preferably, the molecular weight of PDADMAC is Mw 200,000 g / mol, and the molecular weight of PSS is Mw 70,000 g / mol.

5. The method for preparing a dual ion gel electrolyte according to claim 1, characterized in that: In step 3), the high temperature is 30-80° C., preferably 70° C., and the stirring time is 1-3 h, preferably 2 h.

6. A dual-ion gel electrolyte obtained by the preparation method according to any one of claims 1 to 5.

7. A metal ion battery, characterized in that: It comprises a positive electrode, a negative electrode and the double ion gel electrolyte according to claim 6; The positive electrode comprises a positive electrode active material, a conductive agent and a binder; preferably, the conductive agent is CNT; preferably, the binder is PVDF.

8. The metal ion battery according to claim 7, characterized in that: The positive electrode active material is prepared by mixing a conductive material with a potassium Prussian blue material, performing a hydrothermal reaction, ion separation and precipitation, and calcining to obtain the positive electrode active material; Preferably, the conductive material is one of graphene oxide, KPA100 or acetylene black; preferably graphene oxide; The ratio of the conductive material to the potassium Prussian blue material is 1:9; the temperature of the hydrothermal reaction is 100-180°C, and the time is 6-24h; preferably 120°C and 12h; the temperature of the calcination is 600-1000°C, and the time is 6-24h; preferably 800°C and 12h.

9. The metal ion battery according to claim 8, characterized in that: The potassium-based Prussian blue material is KxM[Fe(CN)6]1-y·□·zH2O, wherein □ is a vacancy, M is one or more of Mn, Fe, Co, Ni, Cu, and Zn, 0<x≤2, 0≤y<1, and 0≤z≤5; Preferably, the potassium Prussian blue material is K 1.9 Mn 0.8 Fe 0.2 [Fe(CN)6] 0.96 0.8H2O,. Preferably, the potassium Prussian blue material is prepared in the following manner: a MnSO4 solution is dropped into an aqueous solution of K4Fe(CN)6·3H2O, the mixture is mixed, the resulting solution is washed with water and ethanol, and dried to obtain the potassium Prussian blue material.

10. The metal ion battery according to claim 6, characterized in that: The negative electrode is magnesium metal.